Effect of Phosphorus Modulation in Iron Single‐Atom Catalysts for Peroxidase Mimicking - Ding, Shichao; Barr, Jordan Alysia; Lyu, Zhaoyuan; Zhang, Fangyu; Wang, Maoyu; Tieu, Peter; Li, Xin; Engelhard, Mark H.; Feng, Zhenxing; Beckman, Scott P.; Pan, Xiaoqing; Li, Jin‐Cheng; et al. (Advanced materials (Weinheim), 2024)
Fe–N–C single‐atom catalysts (SACs) exhibit excellent peroxidase (POD)‐like catalytic activity, owing to their well‐defined isolated iron active sites on the carbon substrate, which effectively mimic the structure of natural peroxidase's active center. To further meet the requirements of diverse biosensing applications, SAC POD‐like activity still needs to be continuously enhanced. Herein, a phosphorus (P) heteroatom is introduced to boost the POD‐like activity of Fe–N–C SACs. A 1D carbon nanowire (FeNCP/NW) catalyst with enriched Fe–N4 active sites is designed and synthesized, and P atoms are doped in the carbon matrix to affect the Fe center through long‐range interaction. The experimental results show that the P‐doping process can boost the POD‐like activity more than the non‐P‐doped one, with excellent selectivity and stability. The mechanism analysis results show that the introduction of P into SAC can greatly enhance POD‐like activity initially, but its effect becomes insignificant with increasing amount of P. As a proof of concept, FeNCP/NW is employed in an enzyme cascade platform for highly sensitive colorimetric detection of the neurotransmitter acetylcholine. 1D phosphorus‐doped single‐atom Fe nanowires are designed to mimic peroxidase‐like activity. The mechanism of phosphorus modulation via long‐range interaction for increasing catalytic activity is fully analyzed. The designed single‐atom catalyst exhibits good sensitivity in an enzyme‐cascade sensor platform for colorimetric acetylcholine sensing. This work provides a strategy for creating enzyme‐like single‐atom catalysts and replacing natural enzymes in biomedical applications.